STRATEGI MASYARAKAT MULTIKULTURAL DALAM MEMBANGUN SOLIDARITAS (STUDI KASUS: ETNIS JAWA, BATAK DAN MINANG DI DESA SIPORA JAYA KECAMATAN SIPORA KABUPATEN KEPULAUAN MENTAWAI) - Setyawati, Gita Hermi; Fitlayeni, Rinel; Firdaus, Firdaus (Pendidikan Sosiologi, 2013)
Sipora Jaya people are people who have multicultur that consist of some etnich, where each etnic has different culture value. Although, Sipora Jaya people have many land of etnics but in Sipora Jaya  village  the conflic.  Never happend  between  them, in this  reseacher will discuss about how the strategy of multicultural people in Sipora Jaya village on building and creating  solidarity  between  people  there. Theory  that  used  is  solidarity  social  theory according  to  Emile  Durkheim.  Research  method  that  used  is  case  study  bay  kualitative approach.   The  instrument  date  is  direct  interview and  observaion.  This  research  did  by asking 25 informan, that consist of three different etnics, they one Java, Batak, and Minang that  the  information  were  cellected  by  ceveral  questions.  As  the  result  of  this  research,  it show  several  supporting  factor.  How  people  build  the  solidarity,  they  are  1).  Individual factor,  2). Environment factor,  3). Religion, 4). Force factor. From thore factors, three is a strategy that used by people of Sipora Jaya to build the solidarity. It is a activity that it doing together to create a cooperation and organizations that it be on unity between them. Type of strategy  that  used  to avaid  conflic are  :  1). Cooperaticn  in group of  people.  2). Trust each other. 3). Respecting the norm in sacral environment. 4). Social acticity. 5). Work together.